Pelatihan dan Pendampingan Penyusunan Laporan Keuangan Sederhana di Desa Karanganyar dan Kelurahan Parakancanggah - Ronalisti Adeva Nugrahaeni; Rochmad Bayu Utomo (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2024)
Efficient financial management is a key factor in achieving the success and sustainability of Micro, Small, and Medium Enterprises (MSMEs). However, a major challenge faced by MSMEs is access to the resources and knowledge needed to prepare good financial statements. This Community Service Program aims to provide training on how to make simple financial reports that focus on recording, income, and expenses for business actors in Karanganyar Village and Parakancanggah Village. The goal is to do simple calculations to find out the profits and losses generated from the business. The method used is socialization to educate MSMEs about the importance of preparing financial statements and assistance is applied to assist MSMEs in the practical process of making financial reports. With this community service activity, understanding and skills in preparing effective financial reports can increase significantly